To solve this problem you must appy the proccedure shown below:
1. You have the following function given in the problem above:
f(x)=e^2x
2. You can rewrite is:
y=e^2x
3. Interchange the variables, as below:
x=e^2y
3. The inverse of an exponential function is the logarithm function. Thereforem you have:
ln(x)=ln(e^2y)
ln(x)=2y
4.Then, you have:
y=ln(x)/2
Therefore, the answer is:
f^-1(x)=ln(x)/2
Answer:
x-intercept: (2,0)
y-intercept: (0,-4)
Step-by-step explanation:
x-intercept: when y = 0
2x - 0 = 4
x = 2
y-intercept: when x = 0
2(0) - y = 4
y = -4
Answer:
8.4
Step-by-step explanation:
Answer:
Step-by-step explanation:
Deductive
1. is 19.24
2. is 8,16,24,32,40
3. is associative property of addition